Informal Labor and the Cost of Social Programs: Evidence from 15 Years of Unemployment Insurance in Brazil - François Gerard; Gustavo Gonzaga (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
It is widely believed that the presence of a large informal sector increases the ef?ciency costs of social programs in developing countries. We develop a simple theoretical model of optimal unemployment insurance (UI) that speci?es the ef?ciency–insurance tradeoff in the presence of informal job opportunities. We then combine the model with evidence drawn from 15 years of uniquely comprehensive administrative data to quantify the social costs of the UI program in Brazil. We ?rst show that exogenous extensions of UI bene?ts led to falls in formal–sector reemployment rates due to offsetting rises in informal employment. However, because reemployment rates in the formal sector are low, most of the extra bene?ts were actually received by claimants who did not change their employment behavior. Consequently, only a fraction of the cost of UI extensions was due to perverse incentive effects and the ef?ciency costs were thus relatively small — only 20% as large as in the US, for example. Using variation in the relative size of the formal sector across different regions and over time in Brazil, we then show that the ef?ciency costs of UI extensions are actually larger in regions with a larger formal sector. Finally, we show that UI exhaustees have relatively low levels of disposable income, suggesting that the insurance value of longer bene?ts in Brazil may be sizeable. In sum, the results overturn the conventional wisdom, and indicate that ef?ciency considerations may in fact become more relevant as the formal sector expands
Keywords: 330; Arbeitslosenversicherung; Arbeitsmarkt; Schattenwirtschaft; Brasilien